The influence of hyperbaric oxygen therapy (HBOT) to intercausal relationship between blood vessels, osteoblast, and new bone formation during maxillary suture expansion - Prameswari, Noengki; Sunaryo, Iwa Rahmat; Damaiyanti, Dian Widya; Febrina, Agni (Padjadjaran Journal of Dentistry, 2020)
Introduction: Expansion appliance that can imply tooth movement and opening maxilla suture might affect the blood vessels, bone cells, and formation of the new bone. HBOT accelerated the rate of osteoblast differentiation leading to an increase in bone formation during osteonecrosis. Research about HBOT during maxillary suture expansion has never been investigated. The purpose of this research was to correlate the blood vessels number, osteoblast by administered 2.4 ATA HBOT from day 8-14 to imply new bone formation during maxillary suture expansion. Methods: Eighteen male guinea pigs with randomised post-test only control group design divided into 3 groups. Negative control group K(-), positive control with expansion appliance K(+), expansion appliance and HBOT (P). After 14 days guinea pigs were decapitated. Histological slide of the blood vessels number, osteoblast, and new bone formation were examined under a light microscope then were analysed by regression test. Results: Descriptive test showed increasing blood vessels number, osteoblast, and new bone formation on the administration of HBOT during maxillary suture expansion. Regression test showed that there was a strong correlation between the blood vessels number and osteoblast to the new bone formation with R=6.95 during maxillary suture expansion. Conclusion: 2.4 ATA HBOT influences the intercausal relationship between increasing blood vessels number, increasing osteoblast, and new bone formation during maxillary suture expansion.